Development and technical basis of simplified guidelines for emergency triage assessment and treatment in developing countries. Issue 6 (1st December 1999) - Gove, Sandy; Tamburlini, Giorgio; Molyneux, Elizabeth; Whitesell, Patricia; Campbell, Harry
Abstract : Simplified guidelines for the emergency care of children have been developed to improve the triage and rapid initiation of appropriate emergency treatments for children presenting to hospitals in developing countries. The guidelines are part of the effort to improve referral level paediatric care within the World Health Organisation/Unicef strategy integrated management of childhood illness (IMCI), based on evidence of significant deficiencies in triage and emergency care. Existing emergency guidelines have been modified according to resource limitations and significant differences in the epidemiology of severe paediatric illness and preventable death in developing countries with raised infant and child mortality rates. In these settings, it is important to address the emergency management of diarrhoea with severe dehydration, severe malaria, severe malnutrition, and severe bacterial pneumonia, and to focus attention on sick infants younger than 2 months of age. The triage assessment relies on a few clinical signs, which can be readily taught so that it can be used by health workers with limited clinical background. The assessment has been designed so that it can be carried out quickly if negative, making it functional for triaging children in queues.